Between Empiricism and Teleology in Social Anthropology - Hernández Lefranc, Harold (2025)
An arduous task for the anthropologist as an ethnographer, responsible for carrying out field work, is to delimit (establish limits) and configure (give shape to what doesn’t usually have it), the abundant information that may eventually be accessed. A serious problem is finding the rationality of social processes, that is, finding the causal or concomitance relationships between the heteroclitic factors or variables that make up social processes, which are always historical. Extreme empiricism is an epistemological error, as is what is called teleology. Nominalism as an epistemological strategy and what it implies can be the way to bridge the extremes. The present text, following the brief intellectual biography of a wise man, a character of Borges, offers, helped by some fundamental theorists of the social sciences, some clues that guide to a good conclusion.